Study of freshwater fish fauna and water quality at Paintakli dam from Buldhana district, (M.S) India - Ubharhande, S B; R, Sonawane S (Journal of Experimental Sciences, 2013)
Present investigation is carried out during the study period Jun 2010 to May 2011 to study the fish fauna from Paintakli dam. It is a perennial water resource which used for human consumption, agriculture and fisheries in taluka Chikli and Mahekar, district Buldhana. It is situated approximately 45 km from district Buldhana. In the present study it was observed that the ichthyofauna belong to 07 order 10 families, 19 genus and 21 species, were Cyprinidae family is dominant with 10 (47.61%) species followed by Channidae and Mastacembelidae with 02 (9.52%) species, Balitoridae, Bagridae, Clariidae, Belonidae, Notopteridae, Cichlidae, and Poecilidae contribute 01(4.76%) species each. Finally it may be concluded that the water parameters are within permissible limit and support fish diversity of Paintakli dam were Cyprinidae family which is dominant and still in a position to set a good example of conservation and sustainable management of fish and fishery.